Algas edáficas del trópico. I. Variaciones mensuales de la densidad de algas en un Typic Dystrandept de un cafetal en Costa Rica - Wydrzycka B., Urszula (1983)
The variability of algae density at the surface level of soil in a coffee plantation in the Central Plateau of Costa Rica (1130 m altitude was studied from June 1980 to July 1981. One hundred twenty or one hundred sixty samples were taken each time. The major chemical and physical characteristics of the soil were determined and ecological information for macrovegetation was collected. The highest algae count was obtained during the initial period of the 1981 rainy season (529 313 ± 288 875 cells/g dry soil). During the dry season the number of algae declined greatly and in April 1981 it was 9578 ± 5 693 cells/g dry soil. The dominant group of algae was Chlorophyta due to the great soil acidity. The Bacillariophyta populations were very small and Cyanophyta were encountered only in three months the study, The factors which limit full development of algae during the remainder of the rainy season are discussed.